John of God: An enigma for the medical sciences. - Bonilla, Ernesto (Investigación Clínica, 2014)
Some cures carried out by Medium Jo ío Teixeira de Faría (John of God) are presented. He claims to channel spiritual entities (Drs. Augusto de Almeida, Oswaldo Cruz, and José Valdivino) that have instantaneous access to the physical, emotional and spiritual history of each patient who is then treated by physical or “spiritual” surgeries, herbs, meditation, prayers and the ingestion of “energized” water. People operated on have no pain during the interventions and infections have not been observed. The mechanisms responsible for the healings are unknown